Diffusing Capacity for Carbon Monoxide Predicts Response to Balloon Pulmonary Angioplasty in Patients With Inoperable Chronic Thromboembolic Pulmonary Hypertension - Li, Xin; Zhang, Yi; Luo, Qin; Zhao, Qing; Zeng, Qixian; Yang, Tao; Jin, Qi; Yan, Lu; Duan, Anqi; Liu, Jiaran; An, Chenhong; Ma, Xiuping; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The hemodynamic results of balloon pulmonary angioplasty vary among patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH). Previous studies revealed that microvasculopathy accounted for residual pulmonary hypertension after pulmonary endarterectomy, which could be reflected by the diffusing capacity for carbon monoxide (DLCO). We aimed to identify whether the DLCO could predict the BPA response. Materials and Methods: We retrospectively analyzed 75 consecutive patients with inoperable CTEPH who underwent BPA from May 2018 to January 2021 at Fuwai Hospital. According to the hemodynamics at follow-up after the last BPA, patients were classified as “BPA responders” (defined as a mean pulmonary arterial pressure ≤ 30 mmHg and/or a reduction of pulmonary vascular resistance ≥ 30%) or “BPA nonresponders.” Results: At the baseline, BPA responders had significantly higher DLCO values than nonresponders, although the other variables were comparable. In BPA responders, the DLCO decreased after the first BPA session and then returned to a level similar to the baseline at follow-up. Conversely, the DLCO increased constantly from the baseline to follow-up in nonresponders. Multivariate logistic analysis showed that a baseline DLCO of <70% and a percent change in DLCO between the baseline and the period within 7 days after the first BPA session (ΔDLCO) of > 6% were both independent predictors of an unfavorable response to BPA. Receiver operator characteristic analysis showed that the combination of a baseline DLCO < 70% and ΔDLCO > 6% demonstrated a better area under the curve than either of these two variables used alone. Conclusions: A baseline DLCO < 70% and ΔDLCO > 6% could independently predict unfavorable responses to BPA. Measuring the DLCO dynamically facilitates the identification of patients who might have unsatisfactory hemodynamic results after BPA.